Holistic Management of Cyclothymic Disorder - Sree Lekshmi G A; Yadukrishna T U; Satheesh K; Vinod R (AYUSHDHARA, 2025)
Cyclothymic disorder, sometimes referred to as cyclothymia disorder, characterised by recurrent episodes of depression hypomania and depression. Because cyclothymic disorder is not very severe, it is frequently underdiagnosed. Although the prevalence of this condition is almost equal among men and women, women seem to seek therapy more frequently. Approximately 50% of those with depression who are assessed at outpatient mental health institutions are diagnosed with this disease. This paper deals with a 36-year female patient having presenting complaints of rapid mood changes, not interested in job and irritability every day. The symptoms met the DSM 5 cyclothymia diagnosis criteria. Upon assessment, symptoms predominantly indicative of Kapha dosha imbalance are observed. Consequently, the cyclothymic disorder is considered to be Kaphaja unmada. The HAM A and HAM D scales were used for assessment both before and after therapy. The patient was admitted to the inpatient department of Manorogavijana evam manasika roga and treated with a combination of Panchakarma therapies (internal bio-cleansing therapies), internal medications, motivational counselling, Yogasana (yogic posture), Pranayama (breathing exercise) and relaxation therapy. Patient showed improvement in symptoms after treatment and marked changes noticed on assessment scales.